2015
DOI: 10.25110/arqsaude.v18i2.2014.5175
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos Da Crioterapia vs Correntes Diadinâmicas Na Redução Do Edema De Pata Em Ratas

Abstract: GARNÉS, F. L. dos S.; MARTINS, A. J.; TAKEMURA, O. S. Efeitos da crioterapia vs correntes diadinâmicas na redução do edema de pata em ratas. Arq. Ciênc. Saúde UNIPAR, Umuarama, v. 18, n. 2, p. 107-111, maio/ago. 2014. RESUMO:O edema inflamatório agudo é considerado um problema para a reabilitação, pois acarreta perda da mobilidade e dor, comprometendo a funcionalidade do indivíduo, sendo importante sua diminuição pós-lesão. O presente estudo comparou os efeitos da crioterapia e das correntes diadinâmicas de Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In a different study, edema was induced in the paw of female rats and was treated both by Bernard diadynamic currents (BDC) and cold therapy. Hydropletismography has shown that both treatments were significantly effective to decrease edema, with no difference between them 15 . However, injuries were not caused by peripheral nerve compression, as in our study.…”
Section: Edemamentioning
confidence: 99%
“…In a different study, edema was induced in the paw of female rats and was treated both by Bernard diadynamic currents (BDC) and cold therapy. Hydropletismography has shown that both treatments were significantly effective to decrease edema, with no difference between them 15 . However, injuries were not caused by peripheral nerve compression, as in our study.…”
Section: Edemamentioning
confidence: 99%